Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score (Studi kasus pada PT. Acset Indonusa Tbk dan PT. Nusa Kontruksi Enjiniring Tbk) - Mutiara Kinanti,; Dea Putri Anggraini,; Ratih Kusumastuti, (Manajemen Kreatif Jurnal, 2023)
This study aims to determine the bankruptcy prediction of PT Acset Indonusa tbk and PT Nusa Kontruksi Enjiniring tbk in 2021 using the Altman Z-Score method. The data source used is secondary data, namely in the form of Published Financial Reports of Companies issued by the Indonesia Stock Exchange. This study uses a quantitative descriptive method. The technique used is the Altman Z-Score bankruptcy prediction model with the calculation results that the two companies are in unfavorable results or a dangerous zone so that the two companies are predicted to experience bankruptcy.